A systematic review of thrust manipulation for non-surgical shoulder conditions. Issue 1 (December 2017) - Minkalis, Amy; Vining, Robert; Long, Cynthia; Hawk, Cheryl; de Luca, Katie
Abstract Purpose Although many conservative management options are available for patients with non-surgical shoulder conditions, there is little evidence of their effectiveness. This review investigated one manual therapy approach, thrust manipulation, as a treatment option. Methods A systematic search was conducted of the electronic databases from inception to March 2016: PubMed, PEDro, ICL, CINAHL, and AMED. Two independent reviewers conducted the screening process to determine article eligibility. Inclusion criteria were manuscripts published in peer-reviewed journals with human participants of any age. The intervention included was thrust, or high-velocity low-amplitude, manipulative therapy directed to the shoulder and/or the regions of the cervical or thoracic spine. Studies investigating secondary shoulder pain or lacking diagnostic confirmation procedures were excluded. Methodological quality was assessed using the PEDro scale and the Cochrane risk-of-bias tool. Results The initial search rendered 5041 articles. After screening titles and abstracts, 36 articles remained for full-text review. Six articles studying subacromial impingement syndrome met inclusion criteria. Four studies were randomized controlled trials (RCTs) and 2 were uncontrolled clinical studies. Five studies included 1 application of a thoracic spine thrust manipulation and 1 applied 8 treatments incorporating a shoulder joint thrust manipulation. Statistically significant improvements in pain scores were reported in all studies. Three of 4 RCTs compared a thrust manipulation to a sham, and statistical significance in pain reduction was found within the groups but not between them. Clinically meaningful changes in pain were inconsistent; 3 studies reported that scores met minimum clinically important difference, 1 reported scores did not, and 2 were unclear. Four studies found statistically significant improvements in disability; however, 2 were RCTs and did not find statistical significance between the active and sham groups. Conclusions No clinical trials of thrust manipulation for non-surgical shoulder conditions other than subacromial impingement syndrome were found. There is limited evidence to support or refute thrust manipulation as a solitary treatment for this condition. Studies consistently reported pain reduction, but active treatments were comparable to shams. High-quality studies of thrust manipulation with safety data, longer treatment periods and follow-up outcomes are needed.